Analysis of the Use of Learning Media in English Learning in the Kurikulum Merdeka at SMA Negeri 1 Idanogawo - Angelin Marpaung; Harefa, Trisman; Telaumbanua , Kristof Martin. E; Laoli, Adieli (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
This study investigates the use of learning media in English learning media under the Kurikulum Merdeka at SMA Negeri 1 Idanogawo using a descriptive qualitative method. Data were collected through observations and interviews with English teachers, alongside observations of 11th grade students.The findings reveal that the employment of both digital and conventionalmedia effectively boosts student engagement, motivation, and comprehension. This media utilization is crucial for adapting to the diverse characteristics and needs of the students. However, teachers face notable challenges, including limited technological facilities, inadequate school infrastructur, and insufficient time for designing and implementing innovative media. The choice of learning media is influenced by factors such as facility availability, ease of use, relevance to the material, and suitability for students characteristics. The study underscores the critical need for support from both the school and the government, specifically in the form of training, infrastructure provision, and profesional development, to optimize media usage. Furthermore, it highlights the essential role of teacher creativity in selecting and developing media appropriate for the Kurikulum Merdeka, making learning more effective and adaptive to 21st century demands. Ultimately, the appropriate and innovative use of learnig media can significantly improve the quality of English learning and enhance student competencies at SMA Negeri 1 Idanogawo.